Prevalence of Asymptomatic Bacteriuria among Patients Attending Diabetic Clinic at Fort Port Regional Referral Hospital, Uganda Patients - Wardat Rashid Ali; Alina Peris; Stella Nabirye; Awil Abdi; Nihfadh Tamali; Venance Emmanuel; Dayyabu Shehu (BioMed Target Journal)
The availability of high concentration of sugar in the blood of diabetic patients makes them more susceptible to developing bacterial infections which are asymptomatic commonly referred to as asymptomatic bacteriuria (ASB) than the non-diabetic patients. Diabetes patients with ASB have a much higher risk of developing diabetic complications than individuals without ASB. There is a paucity of data on the burden of ASB and antimicrobial susceptibility in diabetes patients in Uganda. Between March and May 2023, a cross-sectional study was carried out at the Fort Portal Regional Referral Hospital, Uganda outpatient diabetic clinic and 160 diabetes patients were recruited for the study. Mid-stream urine was taken for culture and sensitivity. Data analysis were performed using IBM SPSS version 20. A pie chart was used to display the prevalence and antimicrobial susceptibility patterns of common uropathogens described in frequency and percentages. The overall prevalence of ASB among the study participants was 11%. The most common uropathogen isolated was Escherichia coli, followed by Klebsiella and S. aureus. The most sensitive drug in all the isolates was Nitrofrantoin and resistant drug was Ampicillin. In conclusion, routine testing for ASB and treatment should be according to the antimicrobial susceptibility of diabetic patients.